Food Oral Processing—An Industry Perspective - Devezeaux De Lavergne, Marine; Young, Ashley K.; Engmann, Jan; Hartmann, Christoph (Frontiers in Nutrition, 2021)
We illustrate how scientific understanding of Food Oral Processing enables food product development with specific benefits for several target populations. In vivo, in vitro and in silico approaches are discussed in the context of their ability to quantify oral processing from the molecular to the macroscopic scale. Based on this understanding, food structures with enhanced performance in terms of hedonic and nutritional properties as well as appropriateness for age and certain medical conditions can be developed. We also discuss current gaps and highlight development opportunities from an industry perspective.